2007
DOI: 10.4161/auto.3424
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Autophagy Maturation Step by the MAPK ERK and p38: Lessons from Environmental Carcinogens

Abstract: Previously published online a an Autophagy E-publication: http://www.landesbioscience.com/journals/autophagy/abstract.php?id=3424 KEY WORDSmacroautophagy, autolysosomal maturation, environmental carcinogen, ERK, P38, Sertoli cells ACKNOWLEDGEMENTS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
139
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(148 citation statements)
references
References 17 publications
9
139
0
Order By: Relevance
“…This study showed that resveratrol activated P38 and ERK, but not Akt/mTOR signaling, resulting in the induction of autophagy and the reduction of cell viability. Regarding the function of P38 MAPK in autophagy, abrogation of P38 by chemical inhibitors has been reported to be sufficient to interfere with the normal autophagic maturation step (22,23). Our study showed that P38 was a contributing factor to resveratrol-induced autophagy.…”
Section: Discussionmentioning
confidence: 53%
“…This study showed that resveratrol activated P38 and ERK, but not Akt/mTOR signaling, resulting in the induction of autophagy and the reduction of cell viability. Regarding the function of P38 MAPK in autophagy, abrogation of P38 by chemical inhibitors has been reported to be sufficient to interfere with the normal autophagic maturation step (22,23). Our study showed that P38 was a contributing factor to resveratrol-induced autophagy.…”
Section: Discussionmentioning
confidence: 53%
“…ERK1/2 is not only transiently activated during starvation-induced autophagy 32 but also involved in the formation and the maturation of autophagosomes. 33 Especially, we propose that ERK1/2 may act as a survival signal in Atg5-deficient cells to overcome environmental stress during cell death triggered by oxidative stress. Thus, Atg-dependent autophagic cell death may be further classified as ERK1/2-dependent and -independent cell death.…”
Section: Discussionmentioning
confidence: 96%
“…MAPKs are involved in membrane trafficking, and thus control key steps of phagolysosome biogenesis [44][45][46] and regulate autophagy pathway. 47,48 Some intracellular pathogens hijack MAPK signaling pathways in favor of their survival. For example, intracellular replication of Mycobacterium avium is enhanced by p38 activation, whereas ERK activation has the opposite effect.…”
Section: Discussionmentioning
confidence: 99%